2014
DOI: 10.1055/s-0034-1369881
|View full text |Cite
|
Sign up to set email alerts
|

Patientenverfügung bei Patienten mit Nierenerkrankungen im Vergleich zu allgemein-internistischen Patienten

Abstract: Age was found the more impacting variable than the renal diagnosis on the prevalence of advance directives. Patients with a renal diagnosis should be encouraged to make a statement on dialysis in their living will.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
2
0
2
Order By: Relevance
“…Since September 2009, German law regulates that advance directives - if applicable - must be respected in any decision concerning medical treatment [ 34 ]. In our series, the prevalence of a living will was low, however similar to reports in other medical specialties [ 35 , 36 ]. Their presence had no obvious influence on transition to palliative care.…”
Section: Discussionsupporting
confidence: 90%
“…Since September 2009, German law regulates that advance directives - if applicable - must be respected in any decision concerning medical treatment [ 34 ]. In our series, the prevalence of a living will was low, however similar to reports in other medical specialties [ 35 , 36 ]. Their presence had no obvious influence on transition to palliative care.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, "more advanced age" was independently associated with the existence of one of the documents under study. This has already been confirmed in a variety of studies (13,14). In old age the need is greater for patients to be involved in decisions about the nature and extent of medical interventions (15,16).…”
Section: Discussionmentioning
confidence: 78%
“…A more probable explanation is that not all patients knew exactly what had happened to their documents; it may be that more of the documents should have been presented by relatives. Other studies have also found a relatively low rate of powers of attorney or advance directives either deposited with the hospital or brought into it by the patient or a relative (11,14,20).…”
Section: Discussionmentioning
confidence: 99%
“…Insgesamt 14 Studien konnten keinen statistisch signifikanten Einfluss des Geschlechts bei der tatsächlichen Inanspruchnahme von Vorsorgedokumenten ausweisen [16, 20, 21, 24, 29, 30, 32-34, 36, 40, 41, 44, 47, 53-55]. Zwei der Studien [16,36] fanden zunächst Hinweise auf signifikante Geschlechterdifferenzen, die sich jedoch in anschließenden Regressionsanalysen relativierten, da andere Einflussfaktoren (z. B. das Alter der Befragten) für die Effekte verantwortlich zeichneten.…”
Section: Verbreitung Von Vorsorgedokumenten Bei Frauen Und Männernunclassified
“…mit Geschlecht zu interagieren. So zeigt sich, dass ein höheres Alter [16,24,33,34,36,44,55], ein höherer Sozialstatus [29,30], persönliche Verlusterfahrungen [32][33][34], eigene Kinder [53,54], der Familienstand (verheiratet bzw. in einer Partnerschaft lebend) [24,29,30], eine gefestigte Erwerbssituation [24], das Vorliegen einer (chronischen) Erkrankung [36,44] [29,30,33,34,53,54].…”
Section: Verbreitung Von Vorsorgedokumenten Bei Frauen Und Männernunclassified